THE Effect of Brake Padding Strikes and Reversing Spring Pressure on Acceleration of Drum Brakes - listiyono, listiyono; nurhadi, nurhadi; Md Yusof, Hazlina (PT. ELSHAD TECHNOLOGY INDONESIA, 2023)
Car performance is getting better and better over time. This is thanks to developments in engineering technology. Starting from conventional systems to VVTI technology. What you get is great power with very economical fuel consumption (high efficiency). Even more important is good exhaust emissions. All of this is simply managed by a tool called the ECU (Electronic Computerized Unit). However, this large power output cannot be used properly by a vehicle if it is not equipped with a good chassis system and power scanning system. For this reason, this research will look for/obtain a good chassis system that can match the good engine system to date. The objectives of this research are 1. Is there a big influence of the tensile force of the return lining spring and the stroke of the brake lining on speed acceleration. 2. Look for the right pulling force of the cotton turning spring and the right lining strokes to produce high speed acceleration. The method used in this research is experimental. Meanwhile, the material used is a type of brake lining that is available on the market and is marked with strokes. The reversing spring is set to the desired tensile force. And the research data will be processed using Minitab software. The research results show that: . 1. Scratches on the surface of the brake lining have a big influence on the release of the brake lining from the brake drum wall. By periodically applying strokes to the surface of the canvas, it will increase/maintain vehicle acceleration. 2. The pressure of the brake lining return spring affects the release of the drum brake lining. However, the greater the spring pressure, the more the vehicle's acceleration decreases. 3. Maximum scratches on the drum brake lining surface are 1 (mm). Keywords: Drum Brakes, Spring Style, Drum Brake Pads, Speed ​​Acceleration,